Democratic deficit within the electoral system of the Football Association of the Czech Republic - Michaela Kaprálková (Acta Universitatis Carolinae: Kinanthropologica)
This study analyzes the electoral system of the Football Association of the Czech Republic (FACR) to explore the democratic deficit inherent in its governance structures. Recent trends in Czech football, marked by issues such as corruption and conflicts of interest, highlight the need for optimal governance to enhance accountability and transparency. This research examines the FACR’s new statutes effective from March 2025, comparing them with earlier versions to identify persistent democratic shortcomings. Methodologically, the study employs qualitative document analysis, focusing on the statutory changes and their implications for stakeholder representation and decision-making processes. Key findings indicate that while some reforms aim to mitigate negative practices, the dual Chamber structure and uneven voting rights for different stakeholders undermine genuine democratic participation. Professional players and other vital contributors lack voting rights, leading to a governance model that fails to reflect the interests of all members. The study concludes that without further reforms to address these disparities, the democratic deficit within FACR is likely to persist, limiting the organization’s ability to foster a fair and equitable football environment in the Czech Republic.